2015
DOI: 10.1063/1.4920949
|View full text |Cite
|
Sign up to set email alerts
|

Observation and theory of reorientation-induced spectral diffusion in polarization-selective 2D IR spectroscopy

Abstract: In nearly all applications of ultrafast multidimensional infrared spectroscopy, the spectral degrees of freedom (e.g., transition frequency) and the orientation of the transition dipole are assumed to be decoupled. We present experimental results which confirm that frequency fluctuations can be caused by rotational motion and observed under appropriate conditions. A theory of the frequency-frequency correlation function (FFCF) observable under various polarization conditions is introduced, and model calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
148
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(151 citation statements)
references
References 47 publications
2
148
1
Order By: Relevance
“…A theory for the effects of RISD on 2D-IR spectra was derived in the context of the Stark effect, 45,46 but the essential physical picture is the same even when the ori-gin of the vibrational frequency shifts is not a true Stark effect. Theoretical work has shown that both electrostatics beyond the dipole approximation and chemical interactions like charge transfer play important roles in determining the C − − − N stretching frequency.…”
Section: Temperature-dependent Spectral Diffusion Dynamicsmentioning
confidence: 99%
See 4 more Smart Citations
“…A theory for the effects of RISD on 2D-IR spectra was derived in the context of the Stark effect, 45,46 but the essential physical picture is the same even when the ori-gin of the vibrational frequency shifts is not a true Stark effect. Theoretical work has shown that both electrostatics beyond the dipole approximation and chemical interactions like charge transfer play important roles in determining the C − − − N stretching frequency.…”
Section: Temperature-dependent Spectral Diffusion Dynamicsmentioning
confidence: 99%
“…The contributions of molecular rotation and structural fluctuations of the solvent can be quantitatively separated. [44][45][46] As a starting ansatz, we take the PW-FFCF to be a sum of two frequency fluctuation correlation functions,…”
Section: Temperature-dependent Spectral Diffusion Dynamicsmentioning
confidence: 99%
See 3 more Smart Citations